Women And Hadith: A Thematic Study - Nur Saadah Khair (Journal of Academic Perspectives, 2024)
A thousand years ago, women had a significant role in preserving Hadith of the Prophet and were reported to have had little problems in narrating Hadith, compared to men. Women at that time had equal rights to learn from the Prophet and their contributions to the study of Hadith are something that needs to be acknowledged and appreciated. As a thematic study, this paper aims to address two important themes: first, women who narrated Hadith and second, narrations of Hadith related to women. This paper analyses types of interest among those influential women who were involved in the narration of Hadith, and simultaneously examine the content of Hadith related to women's issues, which were interpreted either positively or negatively. Furthermore, this paper will explore if there is gender bias or misogynistic discourse found in Hadith literature since there are arguments that Hadith demean women's rights and their status in Islam. The methodology used in this research is qualitatively based on data collections from two authoritative books on Hadith; Sahih al-Bukhari and Muslim, and the analytical-critical-approach is used to evaluate the related Hadith. The research outcomes found that (a) most of Hadith narrated by women are not gender biased, (b) numbers of non-anti-women Hadith are higher than anti-women Hadith, and (c) Hadith that has been used to oppress women are probably misunderstood and misinterpreted.